Mesoscale analysis of the transverse cracking kinetics in woven composite laminates using a phase-field fracture theory. (July 2019) - Espadas-Escalante, J.J.; Isaksson, P.
Highlights: Transverse cracking in composite laminates is simulated and compared to experiments. A phase-field approach to fracture is adopted. Both tape and woven composite laminates are considered in this investigation. In woven composites, layer shifting increases the accuracy in the predictions. Oblique cracks observed experimentally are well captured by the model. Abstract: A phase-field approach to fracture is used to simulate transverse cracking kinetics in composite laminates. First, a typical unidirectional tape laminate is modeled and the transverse cracking evolution with the consequent reduction in the in-plane modulus of elasticity is estimated. Then, a four-layered plain weave composite is modeled using different layer shifting configurations. Predictions in the transverse cracking evolution become improved as the shifting configuration of the laminate model become closer to experimental observations. Simulations predict that some cracks do not form perpendicularly to the loading direction, as it has been observed experimentally in similar locations. Only the fracture toughness and the in situ transverse strength of the ply are required without prior knowledge of the position of the cracks or an ad hoc criterion for crack evolution. All the simulations are compared qualitatively and quantitatively to experiments published elsewhere.